Bees at work - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Crop Pollination by Bees K S Delaplane & D F Mayer, CABI Publishing, 2000. 352 pp. ISBN 0851994482 GBP 60 94.25 CABI Publishing Wallingford, Oxon OX10 8DE, UK Fax: +44 1491 829 292 Email: publishing@cabi.org